Nowe ruchy religijne a koncepcje zrównoważonego rozwoju: ekoteologia Wiary Bahá’í - Anoszko , Sergiusz (Studia Europaea Gnesnensia, 2018)
The chief aim of this paper is to outline the concept of sustainable development which is integrated into the doctrine of a relatively novel world religion known as the Bahá’í Faith. The study focuses on the description of causes behind the crisis and potential solutions as they are seen by the Baha’is, by means of analysis of their Sacred Writings and more profound insights into the doctrine, in particular where it concerns ecology and social-economic development.